High‐resolution hyperspectral imaging of diagenesis and clays in fossil coral reef material: a nondestructive tool for improving environmental and climate reconstructions. (30th August 2017) - Murphy, R. J.; Webster, J. M.; Nothdurft, L.; Dechnik, B.; McGregor, H. V.; Patterson, M. A.; Sanborn, K. L.; Webb, G. E.; Kearney, L. I.; Rintoul, L.; Erler, D. V.
Abstract: Hyperspectral imagery (1000–2500 nm) was used to quantitatively map carbonate and clay minerals in fossil reef cores that are relevant to accurately reconstructing past environmental and climatic conditions. Techniques were developed using hyperspectral imagery of fossil reef corals and cores acquired from three different geological settings, and were validated against independent measures of calcite to aragonite ratios. Aragonite, calcite, and dolomite were distinguished using a combination of the wavelength position and asymmetry of the primary carbonate absorption between 2300 and 2350 nm. Areas of core containing small amounts of calcite (>2–5%) were distinguished from aragonite in imagery of two cores, enabling quantitative maps of these minerals to be constructed. Dolomite was found to be the dominant mineral in another core. Trace amounts of the aluminium‐rich clay mineral kaolinite were detected, quantified, and mapped in one core using its diagnostic absorption feature near 2200 nm. The amounts of clay detected from hyperspectral imagery were below the limits of detection by standard X‐ray diffraction techniques but its presence was confirmed by Fourier Transform Infrared Spectroscopy. Hyperspectral imagery acquired at high spatial resolution simplifies vetting procedures for secondary carbonate minerals in coral reef cores, significantly reduces sampling time and costs, and is a powerful nondestructive tool to identify well‐preserved coral aragonite in cores for uses in paleoclimate, paleoenvironment and paleoecosystem reconstruction. Key Points: Nondestructive techniques developed to map and quantify aragonite, calcite, dolomite, and clay in fossil corals and reef cores using hyperspectral imagery The heterogeneity of diagenesis is mapped at high spatial resolutions and low concentrations using the primary carbonate absorption feature A decision tree based on carbonate absorption provides a powerful tool for screening cores for paleoclimate and geochronological studies